Case report: A founder UGDH variant associated with developmental epileptic encephalopathy in Saudi Arabia - Alaamery, Manal; Massadeh, Salam; Aldarwish, Manar; Albesher, Nour; Aljawini, Nora; Alahmed, Othman; Kashgari, Amna; Walsh, Christopher A.; Eyaid, Wafaa (Frontiers in Genetics, 2024)
Congenital disorders of glycosylation (CDG) are a group of more than 100 rare genetic disorders characterized by impaired glycosylation of proteins and lipids. The clinical presentation of CDG varies tremendously, from single organ to multi-organ involvement and from prenatal death to a normal adult phenotype. In this case study, we report a large consanguineous family with multiple children suffering from cerebral palsy, seizure, developmental and epileptic encephalopathy, and global developmental delay. Whole exome sequencing (WES) analysis revealed a homozygous variant in the UGDH gene (c.950G>A; p.R317Q) which segregates with the familial phenotype with a plausible autosomal-recessive mode of inheritance, indicating a potential disease-causing association. The UGDH gene encodes the UDP-glucose dehydrogenase, a key enzyme in the synthesis of specific extracellular matrix constituents (proteoglycans and glycolipids) involved in neural migration and connectivity during early brain development. Many pathogenic mutations of UGDH have been reported in recent literature. However, the variant identified in this study has only been observed in the Saudi population (13 families) and not in any other ethnic background, suggesting that it may be an ancient founder mutation.